Pengaruh Preferensi Belanja Konsumen terhadap Perkembangan Pasar Ciputat di Kota Tangerang Selatan - Nurul Handayani; Kuswanto Nurhadi; Erma Fitria Rini (ARSITEKTURA, 2017)
Ciputat Market is a regional scale traditional market in South Tangerang. In 2002, the construction of shopping centers and modern shops began to grow slowly in the area of South Tangerang. The operation of shopping centers and modern shops are getting closer and outreach to the people, on the one hand it has made it easier for people to buy goods of daily needs, but on the other hand it can impact the development of the traditional market, because consumers have many choices places to shop. The problem of this study was about the changing of consumers shopping preference that can effect the development of Ciputat Market. The purpose of this study was to determine the effect of consumers shopping preferences towards the development of Ciputat Market in South Tangerang. The method used in this research is deductive with descriptive explanative technique analysis. While the data obtained is the result of field observations, questionnaires, and document research. The results of this study shows the preferences of consumer shopping in South Tangerang bases on the location of shopping vebues indicated a tendency to shop in other shopping venues rather than Ciputat market, while the development of the range of services markets tend to stagnate.Keywords: shopping preferences, development of traditional markets